Analysis And Clinical Study Of Surgical Management And Outcome Of Blunt Abdominal Trauma (Indian Journal of Applied-Basic Medical Sciences, 2021)
INTRODUCTION: Trauma during Road Traffic Accident is a major public health problem in all countries. It  causes death, disability or both. 50% die immediately at the time of accident. 25% die in golden  hour (4–6 hours) of trauma. 25% may die late during treatment period due to sepsis and  complications.  AIMS AND OBJECTIVES: 1)To study the impact of blunt abdominal trauma on abdominal solid organs like spleen, liver  and hollow viscera like stomach and intestine along with various mode of injuries and their  different type of management and their outcomes.  MATERIALS AND METHODS: This is a prospective study of blunt abdominal injuries during the period from June 2019 to  January 2021 in Sheth Lallubhai Gordhandas Municipal General Hospital, Ahmedabad.  Number of cases studied is 60. Clinical Data of admitted patient were collected by their detail  history after stabilizing the patient, clinical examination with appropriate investigations.  RESULTS AND DISSCUSION:  In our Study majority of the patients belonged to 21-30 years age group, followed by 31-40  years age group. 46 cases were males, with females accounting for only about 14 cases. 35  patients were operated and 25 patients were selected for non-operative management. Road  traffic accident was responsible for 48% of blunt abdominal trauma cases, while fall from heights accounted for 18% of cases and blow with blunt object was responsible for 34% of  injuries. Majority of the patients presented with abdominal pain (100%) and abdominal  tenderness (76%). Average latent period was between 12-18 hours. Majority of patients (50%)  were taken for surgery between 6-10 hours of latent period. Associated extra abdominal injuries  were found in 27 cases. Apart from routine investigations, abdomen x ray was done in all  patients. Ultrasound of abdomen was done in 53 cases. CT scan was done in 21 cases.  CONCLUSION: Propper clinical examination and appropriate investigations helps in management of patient  either operative or non-operative which leads successful treatment in these patients. Other  associated injuries greatly influence the outcome in morbidity and mortality.
Keywords: Blunt abdominal trauma; Road Traffic Accident; Spleen; Ultrasonography; CECT scan; Conservative Management; Post-operative complications; Mortality